Enantiospecific synthesis of sex pheromone of the obscure mealybug from pantolactone via tandem conjugate addition/cyclization - Hajare, Atul K.; Datrange, Laxmikant S.; Vyas, Samir; Bhuniya, Debnath; Reddy, D. Srinivasa (Tetrahedron Letters, 2010)
An efficient synthesis of an enantiomer of insect's natural pheromone is reported starting from chiral pool D-(-)-pantolactone. Highly stereoselective tandem conjugate addition/cyclization sequence and hydrogenation of exocyclic double bond are the key steps in the present synthesis. (C) 2010 Elsevier Ltd. All rights reserved.